2011
DOI: 10.5114/aoms.2011.22080
|View full text |Cite
|
Sign up to set email alerts
|

Double contrast-enhanced ultrasonography evaluation of preoperative Lauren classification of advanced gastric carcinoma

Abstract: IntroductionThe clinical value of double contrast-enhanced ultrasonography (DCUS) in determining the Lauren classification of advanced gastric carcinoma needed investigation.Material and methodsFifty-eight patients with gastric cancer proved by endoscopic biopsy underwent preoperative DCUS examination in which an oral contrast agent was combined with an intravenous agent, and the findings were compared with the postoperative pathological findings using haematoxylin-eosin and Alcian Blue-Periodic Acid Schiff (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The sensitivity and specificity of heterogeneous enhancement of CEUS in diagnosing undifferentiated gastric cancer were 78.84% and 72.59% respectively. Our previous study also implied that the heterogeneous pattern was more common in diffuse than in intestinal cancers using the Lauren classification [45].…”
Section: Discussionmentioning
confidence: 87%
“…The sensitivity and specificity of heterogeneous enhancement of CEUS in diagnosing undifferentiated gastric cancer were 78.84% and 72.59% respectively. Our previous study also implied that the heterogeneous pattern was more common in diffuse than in intestinal cancers using the Lauren classification [45].…”
Section: Discussionmentioning
confidence: 87%
“…Given the complication of the history of chronic gastritis, abdominal ultrasound was ordered and found that there was nonuniform thickening of the gastric antrum wall. DCEUS has been widely used for diagnosis of gastric cancer in China [4]. It can be used in the preoperative staging of gastric cancer and has been widely applied in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be another strategy that might improve bowel wall diagnostic imaging over that of gray-scale US. 33,[44][45][46][47] However, at present, gastroscopy, CT, and endoscopic US remain the gold standard in tumor characterization and staging.…”
Section: Possible Indications For Eceusmentioning
confidence: 99%